Gestión administrativa en la radio suprema del cantón Vinces - Bajaña García, Nicolle Alexandra (2022)
This proposal has been developed in Radio Suprema Nacional to improve its business management and positioning in the Vinces canton, this company is dedicated to providing advertising services and provides its audience with entertainment through a barium and entertaining radio programming space where they are music, interviews, news, local, provincial, national and international, in order to bring the best variety of radio to its listeners. From the field investigation that was carried out, it was possible to determine that there are important shortcomings in terms of its administration that is decisive to maintain its leadership in the world of radio, which is why this research work seeks to provide the necessary tools to improve its management and use of its resources, as well as provide marketing techniques to expand its good image by establishing lines of work that seek to implement the resources of partners and shareholders. At the beginning, before the possible problem, an analysis of factors that influence the development of the company will be carried out, both internal factors that can cause the lack of training, commitment, and professionalism, and external factors such as legal regulations such as laws. states that establish the radios, and problems by nature that are difficult to counteract, which is why this part is very important since consumers or radio listeners are very sensitive like any consumer when there is an inconvenience, they quickly change their products, which is why the central administration needs several market studies to be able to keep customers always next to the radio.